Perancangan Design UI/UX Aplikasi Pemesanan Kopi Berbasis Android dengan Metode Design Thinking : Studi Kasus: Cafe Qopi - Joko Bintarto (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2026)
The rapid growth of the coffee shop industry has created fierce competition, including for Cafe Qopi. The conventional ordering system that is still in use often triggers queues during peak hours, which has the potential to reduce customer satisfaction and operational efficiency. This study aims to design a user interface and user experience for an Android-based coffee ordering application that is solution-oriented, intuitive, and meets the needs of Cafe Qopi customers. The method used in this study is Design Thinking, a human-centered design approach through five stages: Empathize, Define, Ideate, Prototype, and Test. The Empathize and Define stages are carried out to identify real obstacles faced by users when ordering coffee. Next, the Ideate and Prototype stages are used to design visual solutions and efficient application flows. Final testing is carried out using the System Usability Scale (SUS) or Maze Usability Testing method to measure the level of effectiveness, efficiency, and user satisfaction with the prototype built. Based on the results of testing the Cafe Qopi application prototype on 5 respondents using the System Usability Scale (SUS), an average final score of 83.0 was obtained. Based on the usability test feasibility grouping, this score falls into the Acceptable category with an Excellent Adjective Rating. This indicates that the UI/UX design for the booking application meets usability standards, is easy to operate, and is ready to proceed to the system development stage.